PERKEMBANGAN TEORI TARIF PAJAK EFEKTIF - Teddy Haryadi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This study explores the theory of those that affect the amount of effective tax rates in a company.This study also describes the strategies that can be used by companies in conducting tax management. This study uses a literature review research method. The findings lead to the development of the effective tax rate theories over time, in the past the effective tax rate was considered a negative thing, but the current theory of an effective tax rate can produce something good if it is carried out in accordance with applicable laws. There are several strategies that affect the amount of the effective tax rate that develops from time to time starting from Debt to Total Assets (DAR), Current Ratio (CR), Capital intensity, Company Size. To measure the effective tax rate, you can use the percentage of the current tax divided by profit before tax.